TUSK: a ubiquitin hydrolase complex modulating surface protein abundance in trypanosomes - Yamada, Kayo; Zhang, Ning; Yaqub, Farzana K.; Zoltner, Martin; Field, Mark C. (Frontiers in Parasitology, 2023)
Control of surface protein levels is vital to cellular homeostasis, for maintaining a steady state, to coordinate changes during differentiation and other roles. In African trypanosomes surface proteins contribute to immune evasion, drug sensitivity and environmental sensing. The trypanosome surface is dominated by the GPI-anchored variant surface glycoprotein, but additional GPI-anchored and trans-membrane domain proteins are present with known roles as nutrient receptors and signal transducers. The evolutionarily conserved deubiquitinase orthologs of Usp7 and Vdu1 in trypanosomes modulate the abundance of many surface proteins, including the invariant surface glycoproteins, which have roles in immune evasion and drug sensitivity. Here we identify multiple trypanosome Skp1 paralogs, canonically subunits of cullin E3 ubiquitin ligases, and specifically a divergent paralog SkpZ. Affinity isolation and LCMSMS indicates that SkpZ forms a heterotrimeric complex with TbUsp7 and TbTpr86, a tetratricopeptide-repeat protein. Silencing of SkpZ decreases TbUsp7 and TbTpr86 abundance, confirming a direct association. Further, SkpZ knockdown decreases the abundance of multiple trans- membrane domain proteins but increases GPI-anchored surface protein levels. Hence, a heterotrimeric complex of TbTpr86, TbUsp7 and SkpZ (TUSK), regulates expression levels of a significant cohort of trypanosome surface proteins mediating coordination between TMD and GPI-anchored protein expression levels.